ENTREPRENEURIAL MARKETING DAN KINERJA ORGANISASI PADA UMKM DI TENGAH KETIDAKPASTIAN FAKTOR LINGKUNGAN - Pranatasari, Fransisca Desiana; Wadyatenti, Maria Angela Diva Vilaningrum (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
ABSTRACTMicro, small & medium enterprises (MSMEs) are the main actors that have become one of the pillars of the national economy in developing countries, especially Indonesia. The contribution of MSMEs to the national economy (GDP) is 61.1% and it is able to absorb productive workers in Indonesia. However, the Covid-19 pandemic has had a significant impact on MSME players, which resulted in a decline in Indonesia's GDP and indicated a global economic recession. In this uncertain condition, MSMEs are required to survive with all the resources that they have to maintain their performance and even expected to achieve growth. Entrepreneurial marketing (EM) is a right conceptual approach to implemented in MSMEs in order to maintain MSME performance in uncertain conditions, especially on external environmental factors. The concept of Entrepreneurial Marketing had replaced the traditional marketing concept which had been a business solution. This study provides a conceptual framework and analysis that discusses the role of entrepreneurial marketing that improves organizational performance in the middle of this uncertainty environmental factors in MSMEs from a literature review. Previous research has shown that entrepreneurial marketing has a positive impact on organizational performance in the middle of uncertain environment. Thus, it is hoped that the conceptual model of entrepreneurial marketing can improve the performance of SMEs in the middle of uncertain environment so as to achieve competitive advantage.Keywords: entrepreneurial marketing (EM); organizational performance; uncertainty; environmental factors; micro, small & medium enterprises (MSMEs)ABSTRAKUsaha mikro, kecil & menengah (UMKM) merupakan aktor utama yang menjadi salah satu tonggak perekonomian nasional di negara berkembang khususnya Indonesia. Kontribusi UMKM terhadap perekonomian nasional (PDB) sebesar 61,1% dan mampu menyerap tenaga kerja produktif di Indonesia. Namun, pandemi Covid-19 memberikan dampak yang signifikan bagi pelaku UMKM yang berdampak pada turunnya PDB Indonesia dan mengindikasikan adanya resesi perekonomian global. Dalam kondisi ketidakpastian ini, UMKM dituntut untuk mampu bertahan dengan segala sumber daya yang dimilikinya untuk mempertahankan kinerja mereka bahkan diharapkan mampu mencapai pertumbuhan. Entrepreneurial marketing (EM) merupakan pendekatan konsep yang sesuai untuk diimplementasikan pada UMKM dalam rangka mempertahankan kinerja UMKM dalam kondisi ketidakpastian terutama pada faktor lingkungan eksternal. Konsep entrepreneurial marketing telah meninggalkan konsep pemasaran tradisional yang selama ini menjadi solusi usaha. Penelitian ini memberikan kerangka konseptual dan analisis yang membahas bagaimana peran entrepreneurial marketing terhadap peningkatan kinerja organisasi di tengah ketidakpastian faktor lingkungan pada UMKM melalui literature review. Penelitian terdahulu menunjukkan entrepreneurial marketing mampu memberikan dampak positif pada kinerja organisasi di tengah ketidakpastian lingkungan. Diharapkan model konseptual entrepreneurial marketing pada UMKM dapat meningkatkan kinerja UMKM di tengah ketidakpastian lingkungan sehingga mencapai keunggulan kompetitif.Kata kunci: entrepreneurial marketing (EM); kinerja organisasi; ketidakpastian; faktor lingkungan; usaha mikro, kecil & menengah (UMKM)